Linear Cryptanalysis of SAFER-256 - Kyuregyan, Knarik M. (Mathematical Problems of Computer Science, 2021)
In this paper linear cryptanalysis of 256-bit block cipher SAFER- 256 is presented. SAFER-256 is secure against differential cryptanalysis after 5 rounds.